United States Copyright Law - Open Textbook Library; eLangdell Press Editorial Staff (Open Textbook Library, 2014)
This Intellectual Property Supplement from eLangdell Press contains the text of federal laws and regulations in the area of copyright, trademarks and patents. The editors have endeavored to gather all relevant laws, rules and regulations. This collection is intended to be used primarily as a statutory supplement for law students and legal scholars in academic settings, although practitioners in this area of law will also find it useful. This volume, Volume 1: Copyright Statutory Law contains the text of Title 17 of the United States Code as it appears on the most current edition available on the U.S. Government website FDSYS. Updates to the U.S. Code not yet found in the FDSYS published editions can be found in the United States House of Representatives Office of Law Revision Counsel's Classification Tables. Some formatting modification has been performed to better accommodate electronic readers.
Chapter 1. Subject Matter and Scope of Copyright -- Chapter 2. Copyright Ownership and Transfer -- Chapter 3. Duration of Copyright -- Chapter 4. Copyright Notice, Deposit, and Registration -- Chapter 5. Copyright Infringement and Remedies -- Chapter 6. Importation and Exportation -- Chapter 7. Copyright Office -- Chapter 8. Proceedings by Copyright Royalty Judges -- Chapter 9. Protection of Semiconductor Chip Products -- Chapter 10. Digital Audio Recording Devices and Media -- Chapter 11. Sound Recordings and Music Videos -- Chapter 12. Copyright Protection and Management Systems -- Chapter 13. Protection of Original Designs
In English.
Description based on print resource
Keywords: Law -- Textbooks -- United States; Property Law -- Textbooks